How We Care for Mothers Shapes Who Babies Become: A Support-Based Framework for Maternal Well-Being - Christiana Rebelle (Journal of Prenatal and Perinatal Psychology and Health, 2026)
Maternal well-being is often framed as an individual responsibility, yet it is shaped by the relationships, care experiences, communities, and structural conditions surrounding mothers. This article presents the Support-Based Framework for Maternal Well-Being, a relational and ecological model developed through synthesis of recent literature in the Journal of Prenatal and Perinatal Psychology and Health. The framework organizes support into four interconnected domains: relational support, care experience, community support, and structural and environmental conditions. It argues that support matters not only when available, but when it is timely, accessible, responsive, culturally appropriate, and aligned with a mother’s needs. Because maternal well-being unfolds within the developing mother–baby relationship, support for mothers also shapes the earliest relational and developmental environment for babies. The framework offers practical guidance for research, clinical practice, and policy by shifting the central question from what is wrong with mothers to what mothers need to thrive.